Analysis of Problem-Based Learning Models by Typology of Knowledge Pollock and Cruz (1999) - Iim Imandala; Rumi Li; Agus Supriyadi (Association for Scientific Computing Electrical and Engineering(ASCEE), 2019)
Problem-based learning (PBL) is learning where students build knowledge based on learning experiences to solve problems. This model generally is known by teachers around the world and successfully attracted many researchers. However, very limited study has been conducted to analyze this learning model using the typology of knowledge by Pollock and Cruz (1999). This paper analyzed the PBL model using Pollock and Cruz instrument. This study discovered that learning knowledge and facilities contributed to the success of the learning process. However, the internalism typology instrument recommends for the teacher to select and choose appropriate knowledge. Particularly in specific student experience and scaffolding in constructivism through identification and screening system. Another instrument is externalism typology, found that the absorbs of knowledge depends on the developmental age and group compositions, primarily, in first-third grade students. This instrument suggested that a teacher must be more active to be facilitator and mediator in the absorption of knowledge through the assimilation and accommodations mechanism.